Order Pseudoscorpiones. In: Zhang, Z.-Q. (Ed.) Animal Biodiversity: An Outline of Higher-level Classification and Survey of Taxonomic Richness (Addenda 2013) - Harvey, Mark S. (Zootaxa, 2013)
The classification and diversity estimates of the order Pseudoscorpiones (Harvey 2011) are here updated.  There are 26 Recent families, 454 genera, and 3,533 species; fossil taxa include 1 family, 11 genera, 41 species. Taxon numbers are calculated to the end of 2012.